Optimasi Rute Pendistribusian Produk Bebicare di Kabupaten Sidoarjo dengan Pendekatan Algoritma Genetika - Ema Rosalina; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Distribution is the process of distributing products or services to other parties. Bebicare is an organic baby food product produced by PT. ANUGERAH JAYA MANDIRI. One of the branches of this company is Bebicare Sidoarjo branch. It has 25 outlets that sell products for two and a half hours every day. In the delivery process, there is often a delay in the arrival of products to outlets which results in switching customers to competing products and decreasing sales turnover. The purpose of this study was to find the optimal distribution route for Bebicare products. The method used in the process of finding the optimal distribution route for Bebicare products is to use a genetic algorithm. First, enter the distance data, then the data will be processed using a genetic algorithm, after which the results will be obtained in the form of a distribution route for the Bebicare product. From this study, optimal parameters were obtained in the form of a population of 190, a combination of Cr 0.6 Mr. 0.4, the generations 1150, and the shortest total distance of 118.25 kilometers. The program result route is more optimal than the original route because it has a shorter distance.